System of relations between competitiveness and social cohesion in the European Union (2007–2020) - Eperjesi, Zoltán (Acta Agraria Debreceniensis, 2017)
I my current essay I tried to prove that the European Union modified its economic policy due to the financial and economic crisis and the fierce global competitiveness requirements. The main emphasis was laid on the increase of competitiveness. Competitiveness became preferredto cohesion and the economic and social closing up of the newly joined Middle-Eastern European countries. The funds for competitiveness for growth and employment increase by 6–7% yearly during the financial perspective between 2007–2013. On the contrary the funds for agriculture and rural development decrease by 3% yearly in this period. The tendency remains unchanged during the financial perspective 2014–2020.This tendency strengthens the establishment of the two speed Europe concept and causes tensions between the core regions and the peripheries.